Intellectual Capital Dan Kinerja Keuangan Terhadap Nilai Perusahaan: Pada Industri Perbankan - Fristiani, Nosi lia; Pangastuti, Dyah Ani; Harmono, Harmono (AFRE (Accounting and Financial Review), 2020)
This study aims to examine and provide empirical evidence of the impact of client size and industry specialization on audit quality and the effect of audit quality on audit fees, reputation, and litigation both on audit-detecting misstatement quality and audit-reporting misstatement quality-analyzed based on client factors. This paper utilizes the perspective regulatory theory and signaling theory and is based on quantitative-causality research conducted by the survey method. Technique sampling is performed by purposive sampling. The results indicate that client size had a significant positive effect on the audit quality-detecting misstatement but does not have any impact on the audit quality-reporting misstatements whereas industry specialization auditors have no effect on the audit quality-detecting misstatement but have a significant effect on the audit quality-reporting misstatements.Â Clients may opt for the auditor that charges lower fees but can provide a positive signal for stakeholders or choose an auditor that is registered with BPK or OJK because such audit firms are more acceptable by stakeholders. As for the external auditors, the high-quality audit is necessary to avoid the risk of litigation in addition to maintaining independence. DOI: https://doi.org/10.26905/afr.v3i1.4223